2011
DOI: 10.1080/00288330.2011.587822
|View full text |Cite
|
Sign up to set email alerts
|

Motueka River plume facilitates transport of ruminant faecal contaminants into shellfish growing waters, Tasman Bay, New Zealand

Abstract: Hydrographic and water quality surveys of the Motueka River and its river plume were conducted during a moderate flood event (peak flow of 420 m 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Shellfish populations have declined steeply and Tasman Bay commercial scallop harvest has been suspended since 2005 [130]. Today, prominent economic activities around the bay include aquaculture for green-lipped mussels and livestock ranching (on land) [130][131][132]. Both aquaculture and ranching are private operations that harvest private resources, potentially changing employment opportunities in the bay.…”
Section: Sourcing Stifling Sediment: Teleconnections Between Oyster Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Shellfish populations have declined steeply and Tasman Bay commercial scallop harvest has been suspended since 2005 [130]. Today, prominent economic activities around the bay include aquaculture for green-lipped mussels and livestock ranching (on land) [130][131][132]. Both aquaculture and ranching are private operations that harvest private resources, potentially changing employment opportunities in the bay.…”
Section: Sourcing Stifling Sediment: Teleconnections Between Oyster Bmentioning
confidence: 99%
“…First, sediment is added to the bay mainly through input from terrestrial ecosystems, illustrating the importance of cross-system impacts [140]. Most land use around Tasman Bay is associated with dairy, beef, and sheep ranching, as well as forestry [34,132]. Runoff carrying sediment is directed through prominent currents towards Tasman Bay [140].…”
Section: Sourcing Stifling Sediment: Teleconnections Between Oyster Bmentioning
confidence: 99%
“…The emergence of the use of microbial tracers (e.g. Wyer et al 2009;Cornelisen et al 2011) presents a promising approach for devising experiments to elaborate on the source composition of bacteria in flood-pulses and hence better understand in-stream transport mechanisms.…”
Section: Scale Temporal Dynamics In Responsementioning
confidence: 99%
“…An 'obvious' ramification of these stormflow 'pulses' is that microbially contaminated plumes from the Motueka River represent a major hazard to bivalve shellfish and bathing beaches in Tasman Bay. Accordingly, there has been interest in measuring E. coli dynamics in the lower Motueka River and in the river plume in Tasman Bay (Cornelisen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for E. coli, concentrations of which may be three orders of magnitude higher in stormflows than in baseflows. For example, McKergow and Davies-Colley (2010) found that the faecal microbial load from the whole Motueka catchment was yielded in stormflows, and it is these stormflow plumes that are a particular hazard to swimmers and harvesting of shellfish within Tasman Bay (Cornelisen et al 2011;Wilkinson et al 2011). Concentrations of other water quality variables are less strongly related to flow; however, storm loads may still represent a large proportion of the total loads simply because of the high water volumes discharged.…”
Section: Introductionmentioning
confidence: 99%